Floodplains along the Danube River evaluated with the Floodplain Evaluation Matrix (FEM) determining their importance for flood protection, ecology, and socio-economics - Eder Markus (NATURAL HAZARDS, 2025)
This study presents a method to investigate the influence of active floodplains on flood protection, ecology, and socio-economics. We used and further developed the Floodplain Evaluation Matrix (FEM) to systematically assess the Danube River, known as the most international river worldwide. The study also aims to develop a method applicable to other large rivers, taking into account different data availability and research objectives. Hydrological, hydraulic, ecological, and socio-economic parameters were assessed to address the multiple functions and services of floodplains. The evaluation showed that some active floodplains significantly reduce the impact of a 100-year flood event, with relative flood peak reductions by up to 17% and decelerating the flood wave by up to 41.5 h. While other floodplains may not have a noticeable impact on hydrological or hydraulic parameters, they play a crucial role in preserving biodiversity by providing essential habitats for protected species. We introduced an approach to assess whether a floodplain should be preserved and to categorize the restoration demand as low, medium, or high. Our findings indicate a universal need for preservation and restoration measures across all floodplains, with 81% demonstrating a high or medium demand for restoration. Preservation and restoration of floodplains are integral parts of achieving more sustainable floodplain management for each river. Applying the FEM to other large rivers could create a basis for sustainable decision-making, increase awareness of the multiple benefits of floodplains, and foster the implementation of preservation and restoration measures.